2016
DOI: 10.11646/phytotaxa.278.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tetraselmis verrucosa f. rubens (Chlorodendrophyceae) strains from coastal lagoons of Western Greece using a multivariate approach

Abstract: Strains of Tetraselmis, a genus with systematic and biotechnological interest and one of the most prominent genera in marine phytoplankton, were studied. Five strains of T. verrucosa f. rubens, a taxon first documented in coastal lagoons of Greece, are examined herein under a multivariate approach i.e. in relation to their morphological variability under light and transmission electron microscopy (LM and TEM, respectively), and taking into account certain molecular and biochemical attributes as taxonomic marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Specifically, isolate 5 and culture 57 from Kabira were closely related to T . verrucosa ( ), a free-living strain collected from Messolonghi, Greece ( Chantzistrountsiou et al, 2016 ). Both Japan isolates were well-nested within the T .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, isolate 5 and culture 57 from Kabira were closely related to T . verrucosa ( ), a free-living strain collected from Messolonghi, Greece ( Chantzistrountsiou et al, 2016 ). Both Japan isolates were well-nested within the T .…”
Section: Discussionmentioning
confidence: 99%
“…The red-orange coloration indicated that culture 57 is T . verrucosa f. rubens , however, measurements of both the position and distribution of the chloroplast is needed to identify these isolates ( Chantzistrountsiou et al, 2016 ; Hori, Norris & Chihara, 1983 ). Free-living T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we report for the first time the isolation and polyphasic taxonomy of freshwater green algae strains from Greece belonging to the genera Desmodesmus , Chlorella , Spongiosarcinopsis and Uronema . A small number of Tetraselmis strains have been previously isolated from Greek lagoons [23] but freshwater species have been characterized mainly through microscopic observations [22, 2427] or molecular cloning of the 18S rRNA gene [28, 29]. Most of the TAU-MAC strains (0810, 0910, 1010, 2810, 3110 and 3410) belong to the genus Desmodesmus , one of the most abundant genera in fresh to brackish waters all over the globe [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, a sampling excursion took place in Vistonida Lake at the Nestos Delta lagoonal system in northern Greece, followed by the isolation and characterization of two Tetraselmis Stein (1878) strains. Tetraselmis as a genus is a typical representative of transitional ecosystems, while its biotechnological potential has been extensively reviewed (e.g., [4][5][6][7]). In the past few decades, the presence of the form Tetraselmis verrucosa f. rubens (Butcher) Hori, Norris, and Chihara (1983) has been verified in many Greek coastal lagoons and representatives of the taxon have been taxonomically and biochemically investigated [5].…”
Section: Introductionmentioning
confidence: 99%